(CF3SO3)3Er-decorated black phosphorene for robust ambient stability and excellent flame retardancy in epoxy resin. (1st December 2020) - Qu, Zhencai; Xu, Chang-an; Hu, Zhuorong; Li, Yue; Meng, Huifa; Tan, Zhiyou; Shi, Jun; Wu, Kun
Abstract: Owing to its intrinsic structure, thermal stability and dimension effects, black phosphorene (BP) has great potential in manufacturing advanced-performance polymer composites. However, the shortcoming of instability and re-agglomeration enables great challenges toward its application. Herein, a lanthanide metal ligand ((CF3 SO3 )3 Er) has been employed to decorate few-layer BP nanosheets. By means of density functional theory (DFT), there is a high adsorption energy of −1.49 eV in the system, which confirms a powerful adsorbing effect is existed between BP and (CF3 SO3 )3 Er. Due to the charge transfer from BP to (CF3 SO3 )3 Er molecule, the lone-pair electrons of BP are passivated, thereby the decorated BP (Er-BP) exhibits robust stability in ambient conditions and common solvents. Whereafter, the Er-BP is loading into epoxy resin (EP) to manufacture EP-based composites. The Er-BP can not only effectively enhance the dispersion of BP in EP substrate, but also catalyze the curing process of EP nanocomposites. When the amount of Er-BP in epoxy is 3.0 wt%, the residual char content is clearly improved by 75.42%, which is attributed to the coadjutant catalytic charring function between BP and (CF3 SO3 )3 Er. EP/Er-BP 3.0 sample can meet the requirement of UL-94 V-0 testing, and the limiting oxygen index (LOI) value is improved from 24.7% to 30.3%. Meanwhile, there is a 61.37% reduction in the peak heat release rate (PHRR) and a 36.68% decrease in the total heat release (THR). The smoke production rate (SPR) and total smoke production (TSP) are also decreased by 62.90% and 55.94%, respectively. Particularly, the amount of CO released per second (COP) is dramatically reduced by 74.24%, implying that the heat and smoke release has been significantly suppressed due to the production of protective char layer.